1990
DOI: 10.1002/mrd.1080250212
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the mitochondrial calcium influx and efflux properties are responsible for the decline in sperm calcium during epididymal maturation

Abstract: This study was undertaken to determine the role of calcium ion, a key regulator of the intensity and form of motility in mature demembranated sperm, in the development of motility during passage through the bovine epididymis. Cellular calcium levels in bovine caput and cauda epididymal spermatozoa were measured with three different techniques. 45Ca2+ uptake measurements revealed that net calcium uptake and Ca2(+)-Ca2+ exchange in caput spermatozoa were about 2 to 3 times higher than in caudal spermatozoa. Intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
29
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 27 publications
6
29
0
Order By: Relevance
“…The dramatic fall in extracellular Na C would induce the inhibition of both NHE and NCX, with subsequent accumulation of excess H C and Ca 2C in the sperm cytoplasm, followed by inhibition of the dynein-ATPase by means of the sensors located on ODAs and IDAs, and therefore inhibition of motility. ii) Cytoplasmic Ca 2C in sperm from the caput epididymidis is two to six times higher than that in sperm from the cauda region (Vijayaraghavan & Hoskins 1990). It has been suggested that this could be due to sperm acquisition of ATP2B4 from membranous vesicles in the epididymal luminal fluid during sperm transit throughout the epididymis (Patel et al 2013).…”
Section: Discussionmentioning
confidence: 98%
“…The dramatic fall in extracellular Na C would induce the inhibition of both NHE and NCX, with subsequent accumulation of excess H C and Ca 2C in the sperm cytoplasm, followed by inhibition of the dynein-ATPase by means of the sensors located on ODAs and IDAs, and therefore inhibition of motility. ii) Cytoplasmic Ca 2C in sperm from the caput epididymidis is two to six times higher than that in sperm from the cauda region (Vijayaraghavan & Hoskins 1990). It has been suggested that this could be due to sperm acquisition of ATP2B4 from membranous vesicles in the epididymal luminal fluid during sperm transit throughout the epididymis (Patel et al 2013).…”
Section: Discussionmentioning
confidence: 98%
“…These data strongly suggest that CRISP4, via the regulation of Ca 2+ flow through TRPM8 channels, is involved in defining the functional competence of the sperm acrosome. Electrochemical gradients (K + , Na + , Ca 2+ , H + ) are established in sperm throughout epididymal maturation at or around the transition from caput to the corpus epididymis in the mouse (34)(35)(36). Changes in ion flow have been correlated with the acquisition of specific sperm functions normally manifest during capacitation (3).…”
Section: E)mentioning
confidence: 99%
“…As Ca 2+ readily crosses the plasma membrane (Vijayaraghavan and Hoskins, 1990) it would be necessary for the spermatozoa to either pump excess Ca 2+ out of the cell, or store this cation in subcellular locations such as the acrosome (Dorval et al, 2002). In either case, homeostatic regulation of Ca 2+ would be an energy-dependent process.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in intracellular pH do not drive tyrosine phosphorylation It has been reported in bovine spermatozoa, that intracellular pH [pH]i is a regulator of intracellular calcium [Ca 2+ ]i concentrations (Vijayaraghavan and Hoskins, 1990 (Vijayaraghavan and Hoskins, 1990). Therefore, we examined whether the removal of Ca 2+ from the incubation medium resulted in rise in [pH]i in human spermatozoa.…”
Section: Calcium Negatively Regulates Tyrosine Phosphorylation In Hummentioning
confidence: 99%
See 1 more Smart Citation